(850) A Long Term Policy For Primary Education سياسة طويلة الأجل للتعليم الأساسي - Mahmoud, M. W.; Bishai, Rafka S. (The Institute of National Planning, 2024)
At present, scientific planning has become a vital element, with the state adopting planning as a foundation for building a socially equal society. There should be a well-studied plan for the required remedies in education, as organized education will lead to more qualified and productive results, alongside economic and social development.Since primary education is the base upon which educational stages are built, we have commenced studying this base, considering it essential for all citizens to achieve equality in educational opportunities.This paper primarily aims to introduce a very simple model that directly provides the total enrollment and the number of pupils in each grade after "t" years. Two main points are taken into consideration: The number of new incoming pupils aged six years. The automatic promotion from one grade to another. In the first part of this paper, the annual rates of increase in pupils, in classes, and in the number of new incoming pupils are calculated by fitting regression lines for the period 1958-1965. In the second part, the model is represented in two different ways, depending on the assumptions regarding the expected number of new incoming pupils. For the first, the number follows a geometric progression, while for the second, the number is in an exponential form.